Political Relations of the Kakoi Emirate in the West, the Region of the Mountains - Muhib Qader Mustafa; Qader Muhammed Hassan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
At the end (10th century/4Hijri) a political family in the west mountains region showed up, specifically in Asfahan city, whose King was called (Al Kakoii). Kakoi was a series of Dailami's Kings who were supported by (Sayda Xatoon) the mother of 9 majd Aldawla) in the year (1007/398 Hijri) the last governer of Ray. Were able to create an independent Kingdome in Asfahan City. They were continue till (1051/443Hijri). the creator of this Kingdome was called (Alaa AL Dawla Abo Jaafar Dashmanzayar's son) who took the authority in (1007/398 Hijri) by Sayda Xatoon. he was the cousin of Sayda Xatoon. thats why he was known as Kako's Son, which means uncle in Daylamis accent. however, Ala Al Dawla was commandant till (1041/433 Hijri) and he was able to became a broaden his authority to (Hamadan, Dinawar, Nahawand, Sapoorxwast, and Broojrd) and Kakawayhi are in a good relation with Abbasi and Buawhy's Emperor. they had alson written their names in Fridays speech and on the coins, for thus they were agreed to give them a well-known nicknames, on the other hand their relation was based on protcting and saving their borders. But relations with the Ghaznavids were bad, especially when (Mahmood's) attaching Ray and Mountains region, Alaa Al Dawala King was trying to save his upper hand in Asfahan City, despite from disputation with Ghaznawi's Sultan, but still he was the ruler of Mountains region, when Ghazanwi's broke down and SalJooq's authority, Kakawayhi have lost their political importance and some of the important locations in the mountains like Asfahan and Hamadan. Saljooqs had taken a full authority in (Yazd and Ebrqwa) by Tagrool Beg.